Proximal complete occlusion of right coronary artery presenting with precordial ST-segment elevation: A case report. Issue 41 (October 2016) - Zheng, Jianlei; Lin, Jingyang; Shen, Naiji; Qu, Baiming
Abstract: Background: It is well known that cardiologists empirically judge the culprit lesion of acute ST-segment elevation myocardial infarction (STEMI) according to the corresponding electrocardiographic leads. However, In addition to the obstruction of left anterior descending (LAD) coronary artery, rare cases with the occlusion of proximal right coronary artery (RCA) and/or isolated right ventricular (RV) branch showed the ST-segment elevation in precordial leads V1–V3 as well. Case summary: We reported a patient complaining of acute chest pain and suffering ventricular fibrillation (VF) on admission. The electrocardiogram (ECG) showed mild ST-segment elevation in precordial leads V1–V3 and V4R. Bedside echocardiography displayed normal left ventricular ejection fraction and slight RV dilation. Proximal occlusion of nondominant RCA was confirmed by coronary angiography and urgent percutaneous coronary intervention (PCI) to RCA successfully resolved the chest pain and ST-segment elevation. Conclusion: Undoubtedly, coronary angiography is usually the definite measurement for the diagnosis of culprit lesion. However, bedside echocardiography, ST-segment features in left and right precordial leads, and heart rate will be the additional information for judging ST-segment elevation in precordial leads V1–V3 resulting from occlusion of RCA or LAD.